2021
DOI: 10.1002/advs.202004101
|View full text |Cite
|
Sign up to set email alerts
|

A Lab‐On‐chip Tool for Rapid, Quantitative, and Stage‐selective Diagnosis of Malaria

Abstract: Malaria remains the most important mosquito-borne infectious disease worldwide, with 229 million new cases and 409.000 deaths in 2019. The infection is caused by a protozoan parasite which attacks red blood cells by feeding on hemoglobin and transforming it into hemozoin. Despite the WHO recommendation of prompt malaria diagnosis, the quality of microscopy-based diagnosis is frequently inadequate while rapid diagnostic tests based on antigens are not quantitative and still affected by non-negligible false nega… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 57 publications
(72 reference statements)
0
6
0
Order By: Relevance
“…For instance, especially at the early ring stage of infection, the quantities of hemozoin nanocrystals produced by the parasites are variable, and may affect the resulting magnetization of i‐RBCs. Indeed, we previously showed that the magnetophoretic capture of ring‐stage i‐RBCs does occur, but may imply a slower dynamics than the capture of trophozoites (Giacometti et al, 2021 ). Earlier works exploiting magnetophoretic capture under flow also demonstrated different capture capabilities of the same magnetic‐based setting for different‐stage i‐RBCs, with the ring stage representing the most difficult stage to be detected (Karl et al, 2008 ).…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…For instance, especially at the early ring stage of infection, the quantities of hemozoin nanocrystals produced by the parasites are variable, and may affect the resulting magnetization of i‐RBCs. Indeed, we previously showed that the magnetophoretic capture of ring‐stage i‐RBCs does occur, but may imply a slower dynamics than the capture of trophozoites (Giacometti et al, 2021 ). Earlier works exploiting magnetophoretic capture under flow also demonstrated different capture capabilities of the same magnetic‐based setting for different‐stage i‐RBCs, with the ring stage representing the most difficult stage to be detected (Karl et al, 2008 ).…”
Section: Discussionmentioning
confidence: 99%
“…Further exploitation to implement a diagnostic test for malaria requires integrating i‐RBCs counting, in a way suitable for low‐cost, rapid, and on‐site wide screening of the population in endemic zones. In our strategy (Giacometti et al, 2021 ; Milesi et al, 2020 ), we are implementing this via integrated electrical sensors placed close to the concentrating elements of the chip. However other sensor strategies might be used (e.g., magnetic and optical), as well as resorting to automated pattern recognition of optical images at the focal plane of the chip attraction points.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…One such diagnostic technique that has been developed is known as TMek, a lab-on-a-chip diagnostic method that directly quantifies the level of parasitemia (Fig. 8 ) [ 213 ]. It exploits the magnetic properties of hemozoin (malaria pigment) nanocrystals and provides the quantification value in 10 min [ 213 ].…”
Section: Introductionmentioning
confidence: 99%